2012
DOI: 10.1371/journal.pone.0052348
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Role between p53 and JWA: Prognostic and Predictive Biomarkers in Gastric Cancer

Abstract: Expression of p53 appears to be correlated to prognosis in patients with malignancy, but its role in gastric carcinoma has remained controversial. Recently we reported that JWA, an ADP-ribosylation-like factor 6 interacting protein 5 (ARL6ip5), was both prognostic for overall survival and predictive for platinum-based treatment of gastric cancer. In this study, we aimed to investigate p53 expression as a prognostic and predictive marker in resectable gastric cancer, alone and in combination with JWA. Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
5
13
0
Order By: Relevance
“…Furthermore, our present data revealed that PDCD2 expression was associated with prolonged survival of patients with gastric cancer, whereas p53 expression was associated with poor prognosis of gastric cancer. The latter data were consistent with those of previous literature reports (18,19). The former data are novel and have not been reported by any study in the present PubMed database.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, our present data revealed that PDCD2 expression was associated with prolonged survival of patients with gastric cancer, whereas p53 expression was associated with poor prognosis of gastric cancer. The latter data were consistent with those of previous literature reports (18,19). The former data are novel and have not been reported by any study in the present PubMed database.…”
Section: Discussionsupporting
confidence: 94%
“…Similar to the present study, Chung et al (24) reported that there was no specific genotype of P53 polymorphism in a gastric cancer cohort compared with other groups with or without H. pylori-associated chronic gastritis in a Korean population, though another study by Liu et al identified a significant difference between P53 expression in primary tumor and non-tumor tissue in gastric cancer patients (25). In the gastric cancer group in the current study, the male to female ratio was 1.56, and there was no significant difference in sex distribution between the case and control groups.…”
Section: Discussionsupporting
confidence: 86%
“…Overexpression of mutated p53 has been correlated with pathological parameters of tumour aggressiveness and poor prognosis in human gastric carcinoma [9]. …”
Section: Introductionmentioning
confidence: 99%